1996
DOI: 10.1002/(sici)1097-4628(19960718)61:3<421::aid-app4>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characteristics of two-component polyurethane flame retardant coatings using 2,3-dibromo modified polyesters

Abstract: SYNOPSISTwo-component polyurethane flame retardant coatings were prepared by blending 2,3dibromo modified polyesters (2,3-DBPOs) and polyisocyanate. 2,3-DBPOs were synthesized by polycondensation of 2,3-dibromopropanoic acid, a flame retardant aliphatic carboxylic acid, with 1,4-butanediol, trimethylolpropane, and adipic acid. The content of 2,3-dibromopropanoic acid was varied a t 10, 20, and 30 wt % for the polycondensation reaction. Various physical properties of these new flame retardant coatings were comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…Park et al synthesized two pack polyurethane systems using halogen and phosphorus modified polyesters. Both, halogen and phosphorus containing PU exhibited excellent thermal stability and improved flame retardant properties [19][20][21]. The regular push for developing more environment friendly and low VOC coatings has forced researchers to switch to UV curable and water based coatings.…”
Section: Introductionmentioning
confidence: 99%
“…Park et al synthesized two pack polyurethane systems using halogen and phosphorus modified polyesters. Both, halogen and phosphorus containing PU exhibited excellent thermal stability and improved flame retardant properties [19][20][21]. The regular push for developing more environment friendly and low VOC coatings has forced researchers to switch to UV curable and water based coatings.…”
Section: Introductionmentioning
confidence: 99%
“…Polyurethane‐based coatings are widely used in different industries due to their appropriate properties . These coatings have been utilized as topcoats and one‐coat finishes because of their good resistance to weathering, chemicals, and yellowing .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Park et al synthesized polyester diols with chlorine and bromine side chains, respectively. The results demonstrated that the prepared flame-retardant PU failed to ignite in vertical combustion tests and passed the UL-94 V-0 test [ 50 , 51 ]. Although halogenated flame retardants can provide PU with high flame-retardant efficiency and are inexpensive, halogenated flame retardants emit large amounts of smoke when burned and produce corrosive and toxic gases such as hydrogen halides, dioxins, and furans.…”
Section: Progress Of Flame-retardant Pumentioning
confidence: 99%